Changes in heart rate variability of healthy subjects shortly exposed to printing shop particles and the effect of air purifier intervention. (15th December 2022) - Lyu, Lizhi; Xu, Yu; Wang, Hongbo; Guo, Xin; Gao, Yanjun; Duan, Shumin; Deng, Furong; Guo, Xinbiao; Wang, Yun
Abstract: Particulate matter (PM) released by printers may cause airway inflammation and cardiac electrophysiological changes. We conducted a two-stage crossover study to examine the association between short-term exposure to printing shop particles (PSPs) and the heart rate variability (HRV) among healthy volunteers, as well as to evaluate the effect of air purifier intervention. The on-site assessments of PSPs and individual HRV parameters of the volunteers were used to analyze the influence of size-fractionated PSPs and air purifier intervention on HRV at different lag times after PSPs exposure (0 min, 5 min, 15 min, and 30 min) by using the linear mixed-effects models. We observed that changes in 6 HRV parameters were associated with particle mass concentration (PMC) of PSPs, and changes in 8 HRV parameters were associated with particle number concentration (PNC) of PSPs. The sensitive HRV parameters were the square root of the mean of the sum of the squares of differences between adjacent NN intervals (rMSSD), NN50 count divided by the total number of all NN intervals (pNN50), normalized high frequency power (nHF), very high frequency power (VHF), normalized low frequency power (nLF), and the ratio of low frequency power to high frequency power (LF/HF). Most HRV parameters exhibited the strongest effect associated with PMC and PNC at a lag time of 30 min. The air purifier intervention markedly reduced the PNC and PMC of size-fractionated PSPs, enhanced 5 HRV parameters, and decreased the nLF and LF/HF. Our study suggests that short-term exposure to PSPs can affect HRV parameters, reflecting changes in cardiac autonomic nervous activity, and the use of an air purifier can reduce the concentration of PSPs and improve the autonomic nervous system activity of the exposed individuals. Graphical abstract: Image 1 Highlights: Short-term exposure to printing shop particles (PSPs) affected autonomic function. 8 out of 10 heart rate variability (HRV) parameters changed after exposure to PSPs. Changes of HRV varied by PSPs concentration, PSPs size, and exposure lag time. Air purification reduced PSPs levels and improve HRV parameters.